2011
DOI: 10.1371/journal.pone.0019285
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles for STIM1 and STIM2 in Store-Operated Calcium Entry in Rat Neurons

Abstract: The interaction between Ca2+ sensors STIM1 and STIM2 and Ca2+ channel-forming protein ORAI1 is a crucial element of store-operated calcium entry (SOCE) in non-excitable cells. However, the molecular mechanism of SOCE in neurons remains unclear. We addressed this issue by establishing the presence and function of STIM proteins. Real-time polymerase chain reaction from cortical neurons showed that these cells contain significant amounts of Stim1 and Stim2 mRNA. Thapsigargin (TG) treatment increased the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
117
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 42 publications
8
117
3
1
Order By: Relevance
“…Figure 1D), as now documented by several groups in different types of neurons [4][5][6][7][8]. In fact, depletion of ER and cytoplasmic Ca 2+ is so fast that it partially occludes or masks thapsigargin-mediated ER Ca 2+ release ( Figure 1C).…”
Section: Soce Refers To a Unique Casupporting
confidence: 70%
See 1 more Smart Citation
“…Figure 1D), as now documented by several groups in different types of neurons [4][5][6][7][8]. In fact, depletion of ER and cytoplasmic Ca 2+ is so fast that it partially occludes or masks thapsigargin-mediated ER Ca 2+ release ( Figure 1C).…”
Section: Soce Refers To a Unique Casupporting
confidence: 70%
“…SOCE responses in both cortical and hippocampal neurons (arguably the best studied cell types for SOCE) vary from negligible [5,11], to relatively weak [4,9,12], to levels approaching SOCE activity in non-neuronal cells [6,13,14]. The caveats associated with SOCE detection undoubtedly contribute to these discrepancies, but it is also possible that this variability arises from cell-tocell differences in SOCE activity.…”
Section: Soce Refers To a Unique Camentioning
confidence: 99%
“…Knockdown of STIM2 resulted in even more severe neural differentiation defects than STIM1 knockdown. Notably, both STIM1 and STIM2 contribute to the regulation of Ca 2+ homeostasis in rat neurons but they exhibit distinct functions since STIM2 is mainly involved in regulating the resting level of Ca 2+ in the ER whereas STIM1 prominently activates SOCE [81]. In addition to activating the Orai1 channel, STIM1 can also activate TRPCs and inhibit VGCCs via direct interaction with these proteins [82] [83] [84].…”
Section: The Expression Of Ca 2+ -Binding Proteins During Neural Diffmentioning
confidence: 99%
“…The EF hand domain of STIM2 proteins has significantly lower affinity for Ca 2+ than STIM1, and it has been established that STIM2 proteins primarily control steady-state ER and cytosolic Ca 2+ homeostasis [4]. Both STIM1 and STIM2 proteins are expressed in hippocampal neurons [5], and both of these proteins have been implicated in control of nSOC. Klejman et al observed that STIM1 is colocalized with Orai1 upon depletion of Ca 2+ stores in dendrites and soma [6].…”
mentioning
confidence: 99%
“…However, deletion of both Stim genes resulted in a pronounced impairment in spatial learning and memory and in enhanced LTP [14]. STIM2 is a predominant isoform in the hippocampus [5,15]. Genetic deletion of STIM2 protein impaired SOC and confers protection from neurological damage in a model of focal cerebral ischemia [16].…”
mentioning
confidence: 99%